Values Education for Children in Muslim Families - Mahmudah, Umu; Rohmatunnisa, Awaliyah; Mardlotilah, Nilna; Maysaroh, Nurul Hilda; Anto, Abdul Haris Fitri (Educational Psychology Journal, 2023)
Education of values in children in the family is essential in forming future generations' character and morality. In the context of Indonesian society, knowledge of educational values in Muslim families is critical because of their position as majority community members. Apart from that, efforts to examine the results of empirical research on the theme of values education in Muslim families in Indonesia are still limited. Therefore, this article aims to explore the results of empirical research on the theme of values education in Muslim families and compile them into a narrative. This research uses the scoping review method. Literature exploration sourced from Google Scholar (scholar.google.co.id) with a search range of the last ten years (2013-2023) on 09 November 2023. The literature was selected based on the Preferred Reporting Items for Systematic Reviews (PRISMA) steps. These steps resulted in 23 articles that met the criteria for review. The results of empirical research related to values education for children in Muslim families focus on four themes: implementation of values in the family environment, children's environment, internal family relationships, and the urgency of teaching religion to children. The implications of the results are discussed further.